El crecimiento del comercio en la región Loreto y su relación con la rentabilidad de la caja municipal de ahorro y crédito de Maynas S.A durante el periodo 2007 – 2021 - Ramirez Chufandama, Amalia (2024)
This study analyzes the relationship between economic growth and the financial operations of the Maynas Municipal Savings and Credit Fund in the Loreto region, Peru, during the period 2007-2021. Using a quantitative and non-experimental approach, Spearman's correlation coefficient was used to examine three key hypotheses. The results revealed a moderate correlation between the growth of commerce in Loreto and the profitability of the Municipal Fund, with a Spearman coefficient of 0.450, indicating that, although there is a positive influence of commerce on profitability, there are other significant factors at play. Likewise, a weak but statistically significant correlation (rho of 0.229) was identified between the growth of commerce and direct credits granted by the Municipal Fund. On the other hand, a strong relationship (rho of 0.736) was found between the gross value added of the region and direct deposits in the Municipal Fund. These findings suggest that Loreto's economic dynamics play a crucial role in the financial health of the Municipal Fund, but also highlight the need to consider a diversity of factors in making financial and credit decisions.